Do Measurements of Inner Ear Structures Help in the Diagnosis of Inner Ear Malformations? A Review of Literature. Issue 10 (December 2017) - D'Arco, Felice; Talenti, Giacomo; Lakshmanan, Rahul; Stephenson, Kate; Siddiqui, Ata; Carney, Olivia
Abstract : Objective: We conducted an extensive review of the literature relevant to inner ear measurements in normal and malformative conditions to select reproducible methods and normative ranges that may be used in clinical practice. Data Sources and Study Selection: A review of the published literature was performed in the English language using PubMed with appropriate keywords. We selected only those articles containing normative values of inner ear structures. Data Extraction and Data Synthesis: The following measurements were identified as reproducible and sensitive for the diagnosis of inner malformations: cochlear height in coronal plane; maximal diameter of bony island of lateral semicircular canal; width of vestibular aqueduct: 1) at midpoint; 2) at operculum in axial plane; cochlear canal and cochlear width in multiplanar reconstructions (MPR)/axial; cochlear length. The following cutoffs for normal inner ears are proposed based on the comparative analysis of the literature: cochlea height: >4.3 mm; lateral semicircular canal bony island: >3 mm; vestibular aqueduct: <0.9 (midpoint) and <1.9 mm (operculum); cochlear canal (axial MPR): >1.4 mm and <2.5 mm; cochlear width (MPR): >5.4 mm. Conclusion: Measurements of inner ear structures can help in the interpretation of computed tomography images. They increase the sensitivity in detecting inner ear malformations, especially cochlear hypoplasia now considered more common than previously thought.